HUBUNGAN POWER OTOT TUNGKAI, KEKUATAN OTOT LENGAN DAN TINGGI BADAN TERHADAP KECEPATAN RENANG - Syarifudin, Syarifudin; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problems of this study are: during swimming lectures, based on differences in leg muscle power, arm muscle strength and height of the body with swimming speed with a distance of 50 meters in male students who are caused by differences in sports branches in the student field. The purpose of this study is: to find out whether there is a relationship between leg muscle power, arm muscle strength and height for swimming speed and how much each variable contributes. This research is a quantitative descriptive study with a correlation research method, there are four variables studied namely power, arm strength, height and swimming speed. This correlation study was calculated by bivariate correlation and linear regression. The results of the study of the relationship of power, arm strength and height to swimming speed. The results are: (1) there is a relationship between leg muscle power and swimming speed 0.497> 0.284 with a contribution of 25.6% (2) there is a relationship between arm muscle strength and swimming speed 0.506> 0.284 with a contribution of 25.6% (3 ) there is a relationship between height and swimming speed 328> 0.254 with a contribution of 18.6% (4) there is a relationship between leg muscle power, arm muscle strength and height to the swimming speed of 0.506> 0.284 with a contribution of 45.3%. There is a significant relationship of variable height of 0.506 with a contribution of 45.3%. Thus the significant relationship between leg muscle power, arm muscle strength and height is affected by swimming speed Keywords: Power, Arm Strength, Height, Swimming Speed